Análisis de series temporales y predicción de los parámetros ambientales de la central de generación eléctrica de Tamshiyacu del 2018-2021. Región Loreto – 2021 - Tuesta Perez, Samuel Joseph (2022)
The thesis was developed at the Power Plant of the city of Tamshiyacu, to analyze the evolution of environmental parameters, based on environmental monitoring from 2018-2021. The research is non-experimental, analytical, predictive, horizontal and retrospective. The information was obtained from the semiannual Monitoring Reports of the Environmental Parameters of the Electricity Generation Plant of the city of Tamshiyacu carried out by Electroriente. The analysis of trends and prediction of changes in environmental parameters was carried out, for which the Holt-Winters Model was used. The results for the noise parameter (dB) are within environmental quality standards. In the electric field the values are much lower than the maximum allowed level. Regarding air quality for PM-10 particulate matter, the values are below the maximum allowable level. In Sulfur Dioxide (S02) its values are below the maximum allowed. In Carbon Monoxide (CO) its values decrease; in Hydrogen Sulfide show small fluctuations. In all the parameters evaluated on air quality, concentration levels are shown that are below the National Environmental Quality Standards for Air according to the D.S. No. 003-2017-MINAM. Gaseous emissions of carbon monoxide (CO) present downward and upward fluctuations within normal limits; Nitrogen Oxide (N0) presents ascending and descending values up to a maximum of 890.00 mg/m3N; Carbon dioxide (CO2) has a regular behavior, reaching a maximum value of 9.60 mg/m3N and a slightly decreasing evolution below the value of 7.54 mg/m3N; Finally, the Particles parameter presents an irregular behavior from a minimum value of 6.22 mg/m3N, to a maximum particle concentration of 25.19 mg/m3N and an evolution to increase to values of 31.61 mg/m3N for the next monitoring. The gaseous emissions levels of evaluated parameters show normal emissions in electrical generation equipment.